2017
DOI: 10.1155/2017/4212534
|View full text |Cite
|
Sign up to set email alerts
|

Response of Blood Perfusion at ST 36 Acupoint after Drinking Cold Glucose or Saline Injection

Abstract: Skin blood flux (SkBF) changes caused by drinking cold water are generally associated with vagal tone and osmotic factors in digestive system. According to acupuncture theory, change of SkBF at ST 36 might reflect the functional changes of digestive system. The aim of this study is to analyze the changes of SkBF after drinking 3°C 0.9% saline or 5% glucose injection by monitor blood flux at bilateral ST 36. The results indicated that, after drinking different cold water, the change ratio of SkBF at right side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The blood perfusion flux signal recording and analysis method is described in our previous studies 43 45 . Both thermal stimulation points and control point were marked as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood perfusion flux signal recording and analysis method is described in our previous studies 43 45 . Both thermal stimulation points and control point were marked as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The ECG recording and analysis method is described in our previous studies 9 11 , 43 . The ECG was recorded using the NeurOne system (NeurOne, MEGA electronics Ltd, Finland) at a sampling rate of 1000 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…In the previous study, the coherence analysis along PC meridian was carried out in different aged human before and after 30 mmHg inflating occlusion [ 27 ]. Further study indicated that coherence analysis might be used to assess microcirculatory changes at different ages [ 28 ] and oral load different cold water [ 29 ]. In the current study, the coherence-frequency curves were significantly different after stimulation in the frequency band of 0.8–1.4 Hz, suggesting that Acup and Moxi have different effects on the coherence of BL meridian.…”
Section: Discussionmentioning
confidence: 99%
“…The classic LDFs of both control points (points 1 and 2) were recorded by a PeriFlux 5000 (Perimed AB, Stockholm, Sweden) system with a 64-Hz sample rate. The method used to record and analyze the blood perfusion flux signal is described in our previous studies[2729]. Both thermal stimulation points and control points are shown in Fig 1B.…”
Section: Methodsmentioning
confidence: 99%
“…The ECG was measured by the NeurOne system (NeurOne, MEGA electronics Ltd, Finland). Subjects lay on a comfortable bed, and 3 adhesive Ag/AgCl electrodes (3M, Shanghai, China) were applied to the chest for ECG recording at a sampling rate of 1000 Hz [27, 3436]. The raw data were imported into Kubio HRV software (Kubios HRV Premium 3.0.0, Kubios oy, Kuopio, Finland) in the ASC format, and then the heart rate MSE was analyzed [37], which is described in S1 File.…”
Section: Methodsmentioning
confidence: 99%